Actinic keratosis – state of art. Statement of experts of Polish Dermatological Society - Włodarkiewicz, Adam; Narbutt, Joanna; Adamski, Zygmunt; Chodorowska, Grażyna; Kaszuba, Andrzej; Reich, Adam; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2014)
In recent years we can observe a dynamic increase in skin cancers in whose pathogenesis exposure to ultraviolet radiation (UVR) plays an important role. Actinic keratosis (AK) is a common skin disease, characterized by hyperkeratotic lesions located on skin damaged by UVR (photodamaged skin) or senile skin, most frequently present in people of Caucasian origin. The most frequent risk factors for AK development are: elderly age, male sex, cumulative UVR dose, low skin phototype, living in equatorial regions and long-lasting administration of immunosuppressive agents. In various papers on pathogenesis of AK it was revealed that it is an initial form of lesions leading in consequence to development of skin cancers, especially squamous cell carcinoma (SCC). To date there clinical features of AK predisposing to development of SCC are not known, however, inflammation, diameter over 1 cm, rapid enlargement, bleeding and ulceration are considered as risk factors. AK may spontaneously regress, remain stay stable for many years or progress to SCC. This new concept on pathogenesis of AK caused a new approach to its treatment, with a special emphasis on field of cancerisation, with the use of 5-fluorouracil, imiquimod, photodynamic therapy and ingenol mebutate. In the article we present current knowledge on the pathogenesis of actinic keratosis, a review of therapeutic options and principle rules of prophylaxis.